A költségvetés tervezésének és végrehajtásának a folyamata egy konkrét költségvetési szerv esetében - Holdosi Szabina (2017)
Budgetary institutions are the smallest organisational units of public finances. At the same time, they are the most important element of budgeting in public sector. In the course of their daily operation, they must dispose of complex business related and financial knowledge. From planning to reporting, they take part in budgetary process. The prepara-tion of an annual budget is vital to the operation of budgetary institutions, which is a result of a continuous planning work determining the financial framework of their operation. The Economic, Technical Supplier and Service Provider System of Institutions of Public Education in Szombathely (ETSSPS) is a budgetary organisation of crucial im-portance in the life of the town. In the course of its operation, it carries out the financial, economic and administrative tasks of 18 kindergartens maintained by the Municipality of Szombathely and fulfils the duties related to mass catering in 22 schools and halls of resi-dence. Planning the annual budget takes place by negotiating with the leaders of kinder-gartens. During this, ETSSPS and kindergartens mutually help with each other’s work. When planning the material expenditures of ETSSPS of the Institutions of Public Educa-tion in Szombathely, much emphasis has to be placed on the fees of public utilities as well as the items of purchased nutrition. Planning purchased nutrition needs special attention owing to the per capita support granted by the state. After the labour processes of planning, the annual budget of ETSSPS of the Insti-tutions of Public Education in Szombathely and that of the18 kindergartens have to be registered in the data supplying module KGR K11. KGR K11 is a kind of programme sys-tem with the help of which budgeting as well as data supplies during the year can be pro-cessed in each subsystem of the public finance in compliance with uniform rules. The budget has to be approved by the body governing the entity that is to say by the Municipality of Szombathely until the 28th of February and data have to be supplied to the Treasury. In the course of my investigation, I compared the data concerning the fulfilment of revenues and expenditures in terms of the annual report of ETSSPS of the Institutions of Public Education in Szombathely and Szombathely Kindergarten ‘Friendship’ with the es-timates. During my suggesting hypotheses I examined ETSSPS of the Institutions of Public Education in Szombathely as well as the 18 kindergartens pertaining to its scope of duties in the years 2012 to 2016 from the point of view of the investments and refurbishments completed from their annual budget. As for investments and refurbishments, there are no original estimates in the case of any institutions – despite the fact that, from the day 1st of January, immaterial goods and tangible assets of little value have to be accounted for among investments. As a conse-quence, a lot of tasks have been brought about for the Accounting Department. In the course of my investigations it has been proven that no additional estimates had to be asked for during the year, ETSSPS of the Institutions of Public Education in Szombathely take care of being accurate in their planning the annual budget and following the provisions of the local government in terms of the content requirements prescribed. Changes in legal regulations, however, should be pursued to a greater extent.